Burnout and health behaviors in health professionals from seven European countries - Alexandrova-Karamanova, A.; Todorova, I.; Montgomery, A.; Panagopoulou, E.; Costa, P.; Baban, A.; Davas, A.; Milosevic, M.; Mijakoski, D. (International Archives of Occupational and Environmental Health, 2016)
Within an underlying health-impairing process, work stressors exhaust employees' mental and physical resources and lead to exhaustion/burnout and to health problems, with health-impairing behaviors being one of the potential mechanisms, linking burnout to ill health. The study aims to explore the associations between burnout and fast food consumption, exercise, alcohol consumption and painkiller use in a multinational sample of 2623 doctors, nurses and residents from Greece, Portugal, Bulgaria, Romania, Turkey, Croatia and Macedonia, adopting a cross-national approach. Data are part of the international cross-sectional quantitative ORCAB survey. The measures included the Maslach Burnout Inventory and the Health Behaviors Questionnaire. Burnout was significantly positively associated with higher fast food consumption, infrequent exercise, higher alcohol consumption and more frequent painkiller use in the full sample, and these associations remained significant after the inclusion of individual differences factors and country of residence. Cross-national comparisons showed significant differences in burnout and health behaviors, and some differences in the statistical significance and magnitude (but not the direction) of the associations between them. Health professionals from Turkey, Greece and Bulgaria reported the most unfavorable experiences. Burnout and risk health behaviors among health professionals are important both in the context of health professionals' health and well-being and as factors contributing to medical errors and inadequate patient safety. Organizational interventions should incorporate early identification of such behaviors together with programs promoting health and aimed at the reduction of burnout and work-related stress.